Recent advances on biological mechanism of surgery assisted orthodontic tooth movement - ZHOU Yangyifan; TANG Yi; BIE Miaomiao; KANG Feiwu (Kouqiang hemian waike zazhi)
In adult patients, some teeth move extremely slowly or even stagnate during orthodontic treatment. So how to improve and accelerate the movement of such orthodontic teeth has become a common concern for both patients and doctors. Currently, surgically assisted accelerated orthodontic treatment is a commonly used technique with more accurate results. Studies have shown that its main mechanism is the regional acceleratory phenomenon (RAP), which is a complex physiological response that occurs when bone and soft tissues are stimulated. This article reviews the latest mechanism of RAP in the process of accelerating orthodontic tooth movement during surgery.